Great Lakes Safari Application - Martin Musumba (Uganda Christian University, 2023)
The Great Lakes Safari Travel Application was a transformative digital platform designed to enhance the safari and adventure travel experience in East Africa. While it successfully provided users with immersive access to stunning landscapes, rich wildlife ,and vibrant cultures, it currently lacks a booking feature a critical component for modern travelers. The need for and potential advantages of adding a booking feature to the Great Lakes Safari Travel Application are examined in this research. It explores the user-centric design ideas, iterative development techniques, and feedback integration procedures required for this feature's effective implementation. The study also describes a prototyping procedure to guarantee that the booking function perfectly matches user expectations. By considering the application's technical and operational limitations, the report offers a comprehensive perspective on how the inclusion of a booking feature can elevate the Great Lakes Safari experience. It emphasizes the importance of continuous improvement, scalability, and user engagement to not only meet but exceed customer expectations.
This is a dissertation.